Analisis Perlindugan Hukum Terhadap Pekerja Dalam Sistem Kontrak Kerja Di Indonesia - Tasya Salsabilla; Sultan Maulana Adrian; Syifa Nadiyah Putri; Khilda Nur Azizah; Enjum Jumhana (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study discusses the legal protection for contract workers in Indonesia, which has become increasingly important as the use of contract work systems grows. Although various regulations have been implemented, such as Law No. 13 of 2003 on Manpower and Government Regulation No. 35 of 2021, practice in the field shows gaps in the application of contract workers' rights. This study uses a descriptive qualitative method by gathering data from various literature studies. The results indicate that contract workers often do not receive their full rights, including fair wages, social benefits, and health insurance, due to weak oversight, a lack of understanding among workers about their rights, and non-compliance by companies with applicable regulations. This article identifies several key challenges, such as discrepancies in the interpretation of regulations between central and regional authorities, as well as companies' practices that violate legal provisions. Therefore, there is a need for enhanced supervision, increased worker awareness, and stricter law enforcement to ensure more effective protection for contract workers. The findings are expected to contribute to the development of labor policies in Indonesia that are more supportive of the welfare of contract workers.